Voldtægt og seksuelle overgreb under den sovjetiske besættelse af Bornholm 1945-1946 - Sønderstrup-Andersen, Hans Martin (Fra Krig og Fred, 2026)
Upon the surrender of Nazi-Germany in the beginning of May 1945, Denmark celebrated the liberation after five years of German occupation. However, east of Denmark, in the Baltic Sea, the island of Bornholm did not experience the same kind of freedom. The Soviets - interested in Bornholm because of the island’s strategic placement in the Baltic Sea - threw leaflets from airplanes ordering the Germans to resurrect. However, the German commander refused to surrender to the Soviets allegedly because he wanted to secure a route for German refugees, and his orders was only to capitulate to the Western forces. Consequently, the Soviet Air Force bombed Bornholm’s largest cities, Rønne and Nexø, in order to force Germans to surrender. Red Army Troops were set ashore and after short fights, the Germans surrendered. During the summer of 1945, approximately 8.000 Soviet soldiers were deployed at Bornholm; the islanders had to face a new occupation. During the occupation, there were multiple cases of sexual assault – ranging from minor offences to attempted rape and gang-rape. Often the assaults were brutal and violent and victims suffered through repeated abuse. When the victims addressed the Danish authorities, they were often met with distrust and skepticism. Worse was it, when the Soviet administration came to deal with the cases. They typically denied that a sexual assault had taken place, even in cases characterized by strong evidence. In most cases, the Soviet authorities actively hindered further investigations by claiming the presence of definitive evidence exculpating Soviet soldiers before the Danish police were allowed to investigate allegations against Soviet soldiers. In practice, this placed the Danish police in inescapable dilemma. 5e result was that only a few – if any – perpetrators were punished for their criminal actions. There were claims that one Soviet officer was purportedly executed due to the rape of a Danish woman. However, Soviet documents suggests that the officer was executed on grounds of crimes committed before The Red Army occupation of Bornholm. In all probability, the increase in sexual assaults during the Soviet occupation is due to the effect of war on the soldiers. The literature suggests that preexisting norms were wiped away because of the brutalities of war. Soviet soldiers committed rape against the Danish women, even though, they bore no grudge against Denmark nor were at war with Denmark.